Mid-term Psychiatric Outcomes of Patients Recovered From COVID-19 From an Italian Cohort of Hospitalized Patients - Gramaglia, Carla; Gambaro, Eleonora; Bellan, Mattia; Balbo, Piero Emilio; Baricich, Alessio; Sainaghi, Pier Paolo; Pirisi, Mario; Baldon, Giulia; Battistini, Sofia; Binda, Valeria; Feggi, Alessandro; Gai, Martina; et al. (Frontiers in Psychiatry, 2021)
Background. Although the usual primary clinical manifestation of Coronavirus disease (COVID-19) is respiratory, several non-respiratory symptoms have been described, including neuropsychiatric ones. The aim of this study was to investigate the mid- and long-term mental health outcomes in patients recovered from COVID-19, 3 to 4 months after discharge from the University Hospital Maggiore della Carità, Novara, Italy. Furthermore, we investigated the possible association of the mid-term mental health consequences of the COVID-19 infection with patients’ clinical current status, persistent physical impairment and severity of acute phase of the disease. Methods. Prospective study involving 238 individuals recovered from COVID-19. In the context of a multi-disciplinary approach, patients’ assessment included both a clinical interview performed by an experienced psychiatrist, trained in the use of the Mini-International Neuropsychiatric Interview to assess the presence of anxiety and depressive symptoms and self-administered questionnaires: Beck Anxiety Inventory (BAI), Beck Depression Inventory-II (BDI-II), Resilience Scale for Adults (RSA), Impact of Event Scale (IES). Results. At the psychiatric assessment 32.9% and 29.5% of participants showed anxiety and depressive symptoms, respectively. Changes in appetite and sleep patterns emerged for 15.6% and 31.2% of patients. According to the self-administered questionnaires, 7.1% of participants had moderate-severe anxiety levels (BAI), while 10.5% had mild to severe depression (BDI-II). Twenty-six (11%) participants were referred to further psychiatric consultation. Psychiatric symptoms showed no correlation with acute COVID-19 severity; in our sample patients with depressive symptoms at the clinical interview, as well as those with mild to severe levels of depression according to BDI-II scores, had lower FEV1 values than those without and greater odds for persistent, poor tolerance for physical efforts. Conclusions. As could be expected, an approach including both a psychiatric interview and the use of self-administered questionnaires is likely to capture the psychiatric outcome of patients recovered from COVID-19 better than questionnaires alone. Anxiety and depressive symptoms at follow-up had no correlation with the severity of COVID acute manifestations, but rather with ongoing and persistent physical symptoms. Further studies and longer follow-up duration will allow a better understanding of the complex relationship between residual physical symptoms, quality of life and psychological health.